Developing Organizational Training Impact Scale for workplace training: testing the Malaysian sample to determine the impact of training on organizational effectiveness - Abdul Aziz, Siti Fardaniah; Silong, Abu Daud; Ahmad, Kamsuriah; Selamat, Mohd. Nasir; Roslan, Mohd Reffi Hidayat; Abd Manan, Mohd Ridhwan (Econjournals, 2016)
The aim of this paper is to report the development of Organizational Training Impact Scale (OTIS) for workplace training using the intangible results of training effectiveness. The reason is because instrument that can measure the impact of training on organizational effectiveness is very limited. The OTIS was developed using theories in human resource development, and tested for face validity, content validity, exploratory factor analysis, and reliability. The first version of OTIS comprises of 70 items; however, only 33 items left in the final version. The impact of training before and after training completion was tested using OTIS among the Malaysian civil servant officers; findings indicated a significant different. This has shown that training has impact on organizational effectiveness and can be measured using intangible results.